Influence of the single‐strand linker composition on the structural/dynamical properties of a truncated octahedral DNA nano‐cage family. Issue 10 (October 2014) - Iacovelli, Federico; Alves, Cassio; Falconi, Mattia; Oteri, Francesco; de Oliveira, Cristiano L. P.; Desideri, Alessandro; Walter, Nils G.
ABSTRACT The structural/dynamical properties of three truncated octahedral DNA nano‐cages composed by identical double helices but single strand linkers with different composition, namely 7 thymidines, 7 adenines, and 7 alternated thymidines and adenines, have been investigated through classical molecular dynamics simulations. Trajectories have been analyzed to investigate the role of the linkers in defining nano‐cages stability and flexibility, including possible influence on the internal cages motions. The data indicate that the cages behavior is almost identical and that the structural/dynamical parameters measured along the trajectories are not particularly affected by the presence of different bases. These results demonstrate that the constraints imposed by the nano‐structure geometry are the main factor in modulating these properties. © 2014 Wiley Periodicals, Inc. Biopolymers 101: 992–999, 2014.